Exploring challenges and prospects in the 21st century - Kayadibi, Saim (Association of Muslim Social Scientists, 2009)
The International Conference on Research in Islamic Laws 2009 (ICRIL‘09) was held on 15-16 July 2009 at the University ofMalaya’s (UM) Department of Shari`ah and Law. The 145 presenters focused on the contemporary challenges and prospects in Islamic studies. Zubaidah Ismail director, ICRIL‘09) welcomed the audience and spoke of the importance of Islamic laws; Ibrahim Lembut (director general and chief Shari`ah judge of Malaysia) gave an opening address, and Ahmad Hidayat Buang (director, the Academy of Islamic Studies) declared the event officially opened on behalf of Ghauth Jasmon (vice chancellor, UM).